A Study on Financial Performance of Selected Small and Medium Enterprises of Textile Industries in Tamilnadu - Mr.E.Manikandan; Dr.C. Sengottuvel (Zien Journals, 2021)
The present study aims to identify the financial performance of the small and medium enterprises of textile sector in Tamilnadu by properly establishing relationships between the items of the balance sheet and profit and loss account. The study covers small and medium enterprises of textile industries listed on BSE. The study has been undertaken for the period of ten years from 2011-12 to 2019-20 and the necessary data have been obtained from CMIE database. The liquidity position was strong in case of the selected textile industries thereby reflecting the ability of the enterprises to pay short-term obligations on due dates and they relied more on external funds in terms of long-term borrowings thereby providing a lower degree of protection to the creditors. Financial stability of selected SMEs has showed a downward trend and consequently the financial stability of selected textile industries has been decreasing at an intense rate. The study exclusively depends on the public limited listed companies and it’s published financial data and it does not compare with private limited companies. This is a major limitation of the research. The study is of crucial importance to measure the selected textile industries’ liquidity, solvency, profitability, stability and other indicators that the business is conducted in a rational and normal way; ensuring enough returns to the shareholders to maintain at least its market value. The study will help investors to identify the nature of textile industry and will also help to take decision regarding investment.
Keywords: Financial performance of SMEs; Selected Textile industry in Tamilnadu; performance indicators; Public Limited Listed Companies